The Development of Distributed Learning Techniques in Bhutan and Nepal - Frank Rennie; Robin Mason (International Review of Research in Open and Distributed Learning, 2007)
This paper discusses research and development work currently being conducted with universities in Bhutan and Nepal to design appropriate systems for distance and distributed learning courses among a network of campus sites. Although working from a high level of awareness of pedagogic skills, staff in the region face two significant impediments in the adoption of a more open culture of learning. Firstly, Internet access is improving rapidly, but is still generally too weak and inconsistent to allow any reliance on net-based learning solutions. Secondly, the academic culture is resistant to the recognition of the value of open-learning degrees, with subsequent difficulties in re-designing course materials for a more educationally flexible, student-centred learning environment. Some current pilot initiatives in distributed learning are described. Methods for addressing these two impediments are discussed.